A rhetorical analysis of the joint sitting on the final report of the Truth and Reconciliation Commission held at Parliament on 15 April 2003 - Bucher, Nathalie Rosa (Centre for Rhetoric Studies, 2014)
Includes bibliographical references (leaves 155-164).